STUDI LITERATUR: PEMANFAATAN SUMBER BELAJAR LINGKUNGAN KELAS DALAM PEMBELAJARAN KETERAMPILAN MENULIS TEKS DESKRIPSI DI SD - Ferdian Hardi Nugraha; Dian Indihadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to explore the use of learning resources available around the classroom in teaching descriptive text writing skills at the Elementary School level using a literacy analysis approach. The method applied is qualitative descriptive, with data collection techniques that include researching and evaluating various relevant literature sources, including scientific articles and academic writings published in the past ten years. The data analysis process is carried out through several stages, namely reduction, classification, and synthesis, to produce a comprehensive understanding. The analysis results show that the use of the classroom environment as a learning medium has a positive effect on students' ability to write descriptive. The classroom environment offers real and directly observable objects, thus supporting students in exploring ideas, expanding their vocabulary, and organizing their writing in a more systematic and detailed manner. In addition, utilizing the environment as a learning resource also encourages students' participation and active involvement in learning. Various forms of implementation that have been identified include direct observation activities, recording observation results, discussions, and writing assignments. Nevertheless, there are some obstacles, such as the lack of variety of objects in the classroom and the need for teacher creativity in designing an effective learning process. Therefore, the use of learning resources in the classroom environment can be an alternative teaching strategy that is contextual, innovative, and effective in improving elementary school students' descriptive text writing skills.